TRAINING OF EXPERT PERSONNEL IN THE FIELD OF IRRIGATION IN UZBEKISTAN (1951-1990) - Oybek Kamilovich Komilov,; Risligoy Farkhodovna Khamidova, (EPRA International Journal of Research and Development (IJRD), 2022)
The article reveals the training of specialists in the field of irrigation in Uzbekistan in 1950-1990 at the Tashkent Institute of Irrigation and Agricultural Mechanization Engineers and their contribution to the development of irrigation and agriculture with the help of primary sources. In addition, it was analyzed that the leading positions in the Ministry of Water Resources were occupied by representatives of other nationalities.